LEGAL REGULATION OF THE WASTE MANAGEMENT SYSTEM: PROBLEMS AND SOLUTIONS FOR HARMONIZING INTERNATIONAL STANDARDS AND NATIONAL LEGISLATION - Xudoyberdiyeva Viloyat Jabborovna; Gafurov Rustam Basitovich (Web of Journals Publishing, 2025)
The legal regulation of the waste management system is a key component of environmental governance and sustainable development in the context of increasing anthropogenic pressure on natural resources. Effective waste management requires not only technical and organizational measures but also a coherent and consistent legal framework aligned with international environmental standards. This article examines the main problems and solutions related to the harmonization of international waste management standards with national legislation, with particular attention to the experience and challenges of countries undergoing legal and institutional reforms. International legal instruments, including multilateral environmental agreements, guidelines of international organizations, and best regulatory practices, play a significant role in shaping national waste management policies. However, discrepancies between international norms and domestic legal systems often hinder their effective implementation. The study highlights key legal, institutional, and administrative barriers to harmonization, such as fragmented legislation, insufficient enforcement mechanisms, limited institutional capacity, and gaps in environmental awareness. At the same time, the article emphasizes the importance of adapting international standards to national socio-economic conditions, legal traditions, and governance structures. The research argues that successful harmonization requires an integrated approach combining legislative reform, capacity building, interagency coordination, and public participation. Special attention is given to the role of education and academic institutions in promoting environmental legal culture and supporting evidence-based policymaking. The findings contribute to the understanding of how international environmental law principles can be effectively incorporated into national waste management systems to ensure environmental protection, public health, and sustainable development.
Keywords: Waste management system, environmental law, legal regulation, international standards, national legislation, sustainable development, environmental governance, legal harmonization, institutional capacity, environmental policy.